Fiestel Inspired Structure For DNA Cryptography - Kaundal, Ashish Kumar (My University, 2014)
DNA cryptography is a novel field being taken up by the researcher community for research now a days in order to have secure communication on a network. This technique is inspired from biological science, in which DNA is used as an information carrier from one generation to another. DNA cryptography is preferred for a secure end to end communication due to the vast parallelism and extra ordinary information density that are inherent in any DNA molecule. In this paper previous algorithm based on DNA cryptography is enhanced in terms of its security parameter by incurring feistel inspired structure in it. This adds some sort of confusion and diffusion, which makes it complex enough that it restricts the adversary to perform any kind of brute force attack and hence preserve the confidentiality. The work presented makes use of the most popular Feistel structure for enhancing the encryption process. The results indicate that the feistel inspired structure for DNA cryptography using one time pad for key generation achieves a better encryption (confidentiality) although the cost of increased encryption and decryption time.
ME, CSED
Keywords: DNA CRYPTOGRAPHY; ONE TIME PAD